Global research trends and hot spots on autophagy and kidney diseases: a bibliometric analysis from 2000 to 2022 - Ai, Sinan; Li, Yake; Zheng, Huijuan; Wang, Zhen; Liu, Weijing; Tao, JiaYin; Li, Yaotan; Wang, Yaoxian (Frontiers in Pharmacology, 2023)
Background: Autophagy is an essential cellular process involving the self-degradation and recycling of organelles, proteins, and cellular debris. Recent research has shown that autophagy plays a significant role in the occurrence and development of kidney diseases. However, there is a lack of bibliometric analysis regarding the relationship between autophagy and kidney diseases. Methods: A bibliometric analysis was conducted by searching for literature related to autophagy and kidney diseases in the Web of Science Core Collection (WoSCC) database from 2000 to 2022. Data processing was carried out using R package “Bibliometrix”, VOSviewers, and CiteSpace. Results: A total of 4,579 articles related to autophagy and kidney diseases were collected from various countries. China and the United States were the main countries contributing to the publications. The number of publications in this field showed a year-on-year increasing trend, with open-access journals playing a major role in driving the literature output. Nanjing Medical University in China, Osaka University in Japan, and the University of Pittsburgh in the United States were the main research institutions. The journal “International journal of molecular sciences” had the highest number of publications, while “Autophagy” was the most influential journal in the field. These articles were authored by 18,583 individuals, with Dong, Zheng; Koya, Daisuke; and Kume, Shinji being the most prolific authors, and Dong, Zheng being the most frequently co-cited author. Research on autophagy mainly focused on diabetic kidney diseases, acute kidney injury, and chronic kidney disease. “Autophagy”, “apoptosis”, and “oxidative stress” were the primary research hotspots. Topics such as “diabetic kidney diseases”, “sepsis”, “ferroptosis”, “nrf2”, “hypertension” and “pi3k” may represent potential future development trends. Research on autophagy has gradually focused on metabolic-related kidney diseases such as diabetic nephropathy and hypertension. Additionally, PI3K, NRF2, and ferroptosis have been recent research directions in the field of autophagy mechanisms. Conclusion: This is the first comprehensive bibliometric study summarizing the relationship between autophagy and kidney diseases. The findings aid in identifying recent research frontiers and hot topics, providing valuable references for scholars investigating the role of autophagy in kidney diseases.